Effects of Schyzocotyle acheilognathi (Yamaguti, 1934) infection on the intestinal microbiota, growth and immune reactions of grass carp (Ctenopharyngodon idella). - Pei P Fu (PLoS ONE, 2022)
Our understanding of interactions among intestinal helminths, gut microbiota and host is still in its infancy in fish. In this study, the effects of Schyzocotyle acheilognathi infection on the intestinal microbiota, growth and immune reactions of grass carp were explored under laboratory conditions. 16S rDNA amplification sequencing results showed that S. acheilognathi infection altered the composition of intestinal microbiota only at the genus level, with a significant increase in the relative abundance of Turicibacter and Ruminococcus (P < 0.05) and a significant decrease in the relative abundance of Gordonia, Mycobacterium and Pseudocanthomonas (P < 0.05). Schyzocotyle acheilognathi infection had no significant effect (P > 0.05) on the alpha diversity indices (including Chao1, ACE, Shannon, Simpson index) of intestinal microbiota in grass carp, but PERMANOVA analysis showed that microbial structure significantly (P < 0.01) differed between hindgut and foregut. PICRUST prediction showed that some metabolism-related pathways were significantly changed after S. acheilognathi infection. The relative abundance of Turicibacter was positively correlated with the fresh weight of tapeworm (foregut: r = 0.48, P = 0.044; hindgut: r = 0.63, P = 0.005). There was no significant difference in the body condition of grass carp between the S. acheilognathi infected group and the uninfected group (P > 0.05). Intestinal tissue section with HE staining showed that S. acheilognathi infection severely damaged the intestinal villi, causing serious degeneration, necrosis and shedding of intestinal epithelial cells. The real-time fluorescent quantitative PCR results showed that S. acheilognathi infection upregulated the mRNA expression of the immune-related genes: Gal1-L2, TGF-β1 and IgM.